EDUCATION OF A CHILD BY MUSIC IN THE EARLY PERIOD OF LIFE - Rustamov Feruz Tavakkal ogli; Nurullayev Farrukh Gaybulloyevich (Journals Park Publishing, 2023)
Early age is a variable component of the program and can be changed, supplemented in connection with calendar events and the plan for the implementation of collective and individual musical and gaming features. This educational and methodological complex is designed for 3rd-year full-time students majoring in Music Education. The discipline "music in a preschool educational institution" is included in the national - regional (university) component of the graduate qualification - music teacher cycle.
Keywords: pedagogical psychology, teaching vocal music, motivation of learning, psychology, development of young singers.